FULFILLING CHILDREN'S RIGHTS THROUGH POST-DIVORCE RELATIONSHIPS: An Investigation from Bima - Agustina, Feni (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
This article sheds light on the fulfillment of children's rights after divorce. The fulfillment of children's rights is explained by examining the relationships built by divorced parents. To collect data, interviews were conducted with divorced couples who have children. Taking place in Bima, West Nusa Tenggara, this article identifies at least three patterns of post-divorce parental relationships: (1) the relationship built by both ex-spouses, (2) the relationship built by only one of them, and (3) the relationship that is not built by both ex-spouses. It is arguable to say that the relationship built by both ex-spouses is the best for fulfilling the rights of the child. Conversely, the last type of relationship is mostly ineffective in many cases.[Artikel ini membahas tentang pemenuhan hak-hak anak pasca perceraian. Pemenuhan hak anak dijelaskan setelah meneliti relasi yang dibangun oleh orang tua yang bercerai. Data dikumpulkan dengan melakukan wawancara terhadap pasangan-pasangan yang telah bercera dan memiliki anak. Mengambil tempat penelitian di Bima, Nusa Tenggara Barat, artikel ini menemukan setidaknya terdapat tiga pola relasi orang tua pasca perceraian: (1) relasi yang dibangun oleh kedua mantan pasangan, (2) relasi yang dibangun oleh salah satunya, dan (3) relasi yang enggan dibangun oleh kedua mantan pasangan. Relasi yang dibangun oleh dua mantan pasangan merupakan relasi yang terbaik bagi pemenuhan hak-hak anak. Sedangkan relasi tipe terakhir sama sekali tidak efektif dalam pemenuhan anak.]